Some notes on writing a commentary: Isaiah 1-12 - Groenewald, Alphonso (Verbum et ecclesia, 2009)
I was requested by the editors of the “Historical Commentary on the Old Testament” (HCOT) to contribute two volumes on Isaiah in this series. This present article, however, focuses only on volume I: Isaiah 1-12. The aim of this article can be summarised in six points. Some introductory remarks are made with regard to the genre of commentary writing. Secondly, the viewpoint of the HCOT series is outlined; in other words its methodological and epistemological viewpoint. Thirdly, recent developments in the study of the book of Isaiah are discussed. Fourthly, my own objectives and hypothesis with regard to this project are outlined. Fifthly, a short overview of Isaiah 1-12 on a synchronic level is given. Sixthly, my research methodology is defined as a “diachronically reflected synchronic” reading of the Isaianic text. In the last section some concluding remarks are made.